A Vehicular Cyber-Physical Framework for Studying the Effects of Multiple Disturbances with Application to Connected Autonomous Vehicles - Mohammed Amir; Marine Lincoln; Ramlal Craig; Muddeen Fasil (Transport and Telecommunication)
Cyber-physical systems (CPSs) are considered a new era of complex systems that harness the integration of computational and physical capabilities to facilitate interactions between humans via different mediums, creating systems that are smarter and more efficient. These systems underpin critical infrastructures (CIs), which require coordination to achieve societal functions. However, the exponential growth of CPSs brings about a new challenge as it relates to the security of such systems and by extension any disturbances which might affect their operation. Inherently, CPSs are sophisticated systems comprising several subsystems, integrated to facilitate functionality. Thus, creating a situation whereby different vulnerabilities may be present, leading to potential cyberattacks. Cyberattacks have become prevalent and complex within society, leading to loss of resources or worse life-threatening events. The authors propose a Vehicular Cyber Physical System (VCPS) framework for studying the effects of Cyberattacks, Communication Impairments, and Sensor Faults with application to Connected Autonomous Vehicles (CAVs). The proposed framework can be used for understanding the effects of multiple disturbances on platooning and by extension serves as a good platform for the development of resilient control strategies.